1998
DOI: 10.1001/archopht.116.5.577
|View full text |Cite
|
Sign up to set email alerts
|

Activated Protein C Resistance, Factor V Leiden, and Central Retinal Vein Occlusion in Young Adults

Abstract: To confirm the relationship between resistance to activated protein C (APC), factor V Leiden, and central retinal vein occlusion in young adults as reported in a recent study of patients younger than 50 years. Patients and Methods: Patients younger than 50 years with central retinal vein occlusion were identified from the medical records of the Wills Eye Hospital Retina and Retina Vascular Services. Blood samples were taken from each patient and analyzed for resistance to APC and identification of factor V Lei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
2
5

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 21 publications
(16 reference statements)
3
49
2
5
Order By: Relevance
“…In previous studies, the rate of activated protein C resistance was found to be higher in patients with CRVO compared to normals and was thought to contribute to the etiopathogenesis of CRVO (Williamson et al 1996;Larsson et al 1996). Recently, after the identification of the genetic defect which causes activated protein C resistance (factor V Leiden), the frequency of the mutation in CRVO patients was not found to be higher than in the normal controls (Larsson et al 1996;Demirci et al 1997;Hodgkins et al 1995;Gottlieb et al 1998). The controversy surrounding this data was thought to be caused by either low sensitivity of the APCR assays or conditions like pregnancy, oral contraceptive use and positive lupus anticoagulant which cause secondary APCR (Vine & Samama 1997).…”
Section: Discussionmentioning
confidence: 98%
“…In previous studies, the rate of activated protein C resistance was found to be higher in patients with CRVO compared to normals and was thought to contribute to the etiopathogenesis of CRVO (Williamson et al 1996;Larsson et al 1996). Recently, after the identification of the genetic defect which causes activated protein C resistance (factor V Leiden), the frequency of the mutation in CRVO patients was not found to be higher than in the normal controls (Larsson et al 1996;Demirci et al 1997;Hodgkins et al 1995;Gottlieb et al 1998). The controversy surrounding this data was thought to be caused by either low sensitivity of the APCR assays or conditions like pregnancy, oral contraceptive use and positive lupus anticoagulant which cause secondary APCR (Vine & Samama 1997).…”
Section: Discussionmentioning
confidence: 98%
“…Three smaller studies however with only 14, 21 and 35 patients each with CRVO failed to identify any patients with these deficiencies. [20][21][22] A controlled population study with 69 patients with CRVO compared to a normal matched population showed ATIII levels were significantly lower (although still within the normal range) in normal controls than patients! 23 Superficially it appears that there may be an association between CRVO and deficiency of these naturally occurring anticoagulants.…”
Section: Protein C Protein S and Anti-thrombin Iii Deficiencymentioning
confidence: 99%
“…17,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Although many studies suggest an increased frequency of APCR/FVL in patients with CRVO only two out of nine studies in which the incidence of APCR/FVL is compared with a normal cohort is there a significantly increased incidence of this abnormality. Surprisingly both of these studies included patients of any age where one would have anticipated an association with younger patients.…”
Section: Factor V Leiden/activated Protein C Resistancementioning
confidence: 99%
“…O tratamento com o interferon também está associado a risco aumentado de diabetes e hipertrigliceridemia, e pode ser um fator de risco adicional ao estado de hipercoagulabilidade (25) . Muita discussão faz-se sobre a necessidade de exames rotineiros em todos os pacientes em uso destas medicações (15,26) e a necessidade de descontinuação aos primeiros sinais da retinopatia (14) . Na população geral, as lesões têm incidência baixa, são na sua maioria assintomáticas e desaparecem sem deixar seqüelas em uma grande porcentagem dos pacientes, mesmo com a manutenção do tratamento (14)(15) .…”
Section: Relato Do Casounclassified